PENYIDIKAN TINDAK PIDANA PERAMBAHAN HUTAN BERDASARKAN UNDANG-UNDANG NOMOR 18 TAHUN 2013 TENTANG PENCEGAHAN DAN PEMBERANTASAN PERUSAKAN HUTAN OLEH DIREKTORAT RESERSE KRIMINAL KHUSUS KEPOLISIAN DAERAH RIAU - Dewa Ayu Putu Laksmi; Erdianto Effendi; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Lately, the destruction of forests has become more widespread and complex. The destruction occurs not only in production forests but has also penetrated into protected forests or conservation forests. Forests encroachment is a forest clearing activity for the purpose of owning, controlling, and utilizing forest product regardless of the basic function carried by a forest area. Illegal occupation of forest land, forest use deviating from its function, and irresponsible forest exploitation are severely damaged. The losses incurred by forest encroachment are enormous, the country losing billion and even trillions of rupiah. In addition to economic losses of forest products taken by encroachers uncontrollably and ignoring sustainable principles, the enormous environmental damage is very large and has extraordinary impact on forests ecosystem imbalances.This study uses a kind of sociological juridical research that sees the correlation between law and society. This research was conducted at Sub Directorate IV of Directorate of Special Criminal Investigation of Riau Regional Police, while population and sample are all related parties in problem to be studied. Sources of data used, primary data, secondary data, and tertiary data, data collection techniques in this study by interviews, and literature review.From the research there are three main points that can be concluded. The first, criminal investigation of forest encroachment based on Law Number 18 of 2013 on Prevention and Eradication of Forest Destruction by Directorate of Special Criminal Investigation of Riau Regional Police, is still not running properly that has been regulated in legislation. Secondly, obstacles in the criminal investigation of forest encroachment based on Law Number 18 of 2013 on Prevention and Eradication of Forest Destruction by Directorate of Special Criminal Investigation of Riau Regional Police, are financial obstacles, obstacles of facilities and infrastructure, obstacles to bring in forestry experts, lack of public legal awareness, and geographical factor. Third, efforts to overcome obstacles in the criminal investigation of forest encroachment based on Law Number 18 of 2013 on Prevention and Eradication of Forest Destruction by Directorate of Special Criminal Investigation of Riau Regional Police, are propose additional operational costs, adding facilities and infrastructure, coordinate or communicate with experts, and raising public awareness of forest legislation.Key Words: Investigation – forestry crime – forest encroachment